Dairy cow reproduction under the influence of heat stress. Issue 4 (29th November 2019) - Sammad, Abdul; Umer, Saqib; Shi, Rui; Zhu, Huabin; Zhao, Xueming; Wang, Yachun
Abstract: Dairy farming is vulnerable to global warming and climate change. Improving and maintaining conception rates (CRs) have a paramount importance for the profitability of any dairy enterprise. There is an antagonistic relationship between fertility and milk yield, and intensive selection for milk yield has severely deteriorated reproductive efficiency. Irrespective of geography and husbandry, modern dairy cows experience heat stress (HS) effects leading to fertility declines, but it worsens in tropical climates. The threshold of HS experience among modern dairy cow has lowered, leading to decreased thermal comfort zone. Studies show that this threshold is lower for fertility than for lactation. HS abatement and robustness response to lactation yield lead to negative energy balance, and cow's reproductive requirements remain unfulfilled. The adverse effects of HS commence from developing oocyte throughout later stages and its fertilization competence; the oestrus cycle and oestrus behaviour; the embryo development and implantation; on uterine environment; and even extend towards foetal calf. Even cows can become acyclic under the influence of HS. These harmful effects of HS arise due to hyperthermia, oxidative stress and physiological modifications in the body of dairy cows. Proper assessment of HS and efficient cooling of dairy animals irrespective of their stage of life at farm is the immediate strategy to reduce fertility declines. Other long‐ and short‐term mitigation strategies to reduce fertility declines during HS include feeding care, reducing disease and mastitis rates, using semen from cooled bulls, timed artificial inseminations (AI), allied hormonal interventions and use of embryo transfer technology. Ultimate long‐term solution should be well‐planned breeding for fertility improvement and HS tolerance.